An Integration of Wining People’s Heart Based on Buddhism - KaeoRuan, Chinchai (Journal of International Buddhist Studies, 2023)
Human are social animals, they are members of a group for the reasons of security. In this respect, it seems to be living in a human society result the positive way, but the fact that there are many details of living in the society. All human have the driving force in their mind that represent as greed, hatred and ignorance. These driving forces are causing the harmful action and result the social problem and weak society. For this reason, the laws (moralities) are needed to control the human behavior in society to the extent appropriate, not to make trouble for others. On the other hand, only performing of nonviolence is not enough for complex society, because of the encroachment is only a problem that needs to be solved. The aim of surviving for oneself only by ignoring the suffering of others, a member of society, it is the same problem.